Investigation of new biomarkers of kidney injury in renal transplant recipients undergoing graft biopsy. Issue 9 (8th July 2021) - Michon, Arthur; Durrbach, Antoine; Gautier, Jean‐Charles; Benain, Xavier; Lunven, Catherine; Jagerschmidt, Alexandre; Aubert, Catherine; Poetz, Oliver; Joos, Thomas; Gury, Thierry; Becquemont, Laurent
ABSTRACT: Aim: Urinary and blood kidney biomarkers (BM) remain insufficient for early kidney injury detection. We aimed to compare new kidney BM with histopathological data in kidney allograft recipients. Methods: Blood and urine samples were collected from consecutive adult patients just before graft biopsy. All kidney samples were classified according to the Banff 2007 classification. The diagnostic performance of 16 new BM was compared to those of urinary proteins, blood urea nitrogen, eGFR, and serum creatinine to identify histopathological groups. Results: Two hundred and twenty‐three patients were analyzed. Microalbuminuria and urinary proteins performed well to discriminate glomerular injury from slightly modified renal parenchyma (SMRP). Urinary neutrophil gelatinase‐associated lipocalin (NGAL) had the best performance relative to SMRP (AUROC .93) for acute tubular necrosis (ATN) diagnosis. Other BM had a slightly lower AUROC (.89). For the comparison of ATN to acute rejection, several new urinary BM (NGAL, cystatin C, MCP1) and classical BM (eGFR, serum creatinine) gave similar AUROC values (from .80 to .85). Urinary NGAL values in patients with ATN were 10‐time higher than those with acute rejection ( P =.0004). Conclusion: The new BM did not outperform classical BM in the context of renal transplantation. Urinary NGAL may be useful for distinguishing between ATN and acute rejection.